The Efficacy of Taurolidine Citrate Solution v Heparin Lock Solution Instilled in Catheter Lumens of End Stage Renal Disease - Rizwan Elahi, M. Hasan Siddiqui, M. Asim Rana, M. Ahad Qayyum, Waseem Iqbal, M. Sohail Khalid, R. Pervaiz, M. Mansoor Hafeez (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Hemodialysis patients with end-stage renal illness use a tunnelled central vein catheter for vascular access. Heparin with a preservative, in contrast, exhibits inferior antibacterial effects against biofilm and plank tonic bacteria. Aim: To evaluate the effectiveness of taurolidine citrate solution versus heparin lock solution when infused into the catheter lumens of hemodialysis patients with end-stage renal illness. Study design: Randomized clinical trial Place and duration of study: Hemodialysis Unit, King Fahad Specialist Hospital, Buraidah, Saudi Arabia from 11th December 2018 to 10th June 2019. Methodology: One hundred and fourteen patients on hemodialysis aged 40-70 years with end stage renal disease with Glomerular filtration rate (GFR) less than 15 mL/min, on maintenance hemodialysis through tunnelled dialysis catheter dependent for at least 6 months and patent catheters were selected and randomized into two equal groups by using sealed opaque envelopes bearing a tag of Heparin group and citrate-taurolidine group. Patients were excluded from the study if they had a catheter site infection or an infection unrelated to a catheter that was on antibiotic therapy or had positive blood cultures within two weeks of enrollment. Every two weeks and at the time the catheter was removed, blood cultures were routinely obtained from the catheter lumen to look for bacterial colonization. At the conclusion of six months of hemodialysis, the CRI was assessed. All instances of infections caused by catheters were documented. Results: Incidence of catheter related infection occurred in 5 (8.8%) patients who underwent Heparin group while none of the patient (0%) of taurolidine/citrate group suffered with catheter related infection. This data reveals significantly high incidence of CRI in Heparin group (p=0.029) and significantly high efficacy of taurolidine/citrate group over Heparin group. Conclusion: Efficacy of taurolidine citrate solution is superior versus heparin lock solution instilled in the catheter lumens of patients on hemodialysis. Keywords: Catheter, Infection, Renal disease, Hemodialysis